2021
DOI: 10.3390/cells10020461
|View full text |Cite
|
Sign up to set email alerts
|

DNA or Protein Methylation-Dependent Regulation of Activator Protein-1 Function

Abstract: Epigenetic regulation and modification govern the transcriptional mechanisms that promote disease initiation and progression, but can also control the oncogenic processes, cell signaling networks, immunogenicity, and immune cells involved in anti-inflammatory and anti-tumor responses. The study of epigenetic mechanisms could have important implications for the development of potential anti-inflammatory treatments and anti-cancer immunotherapies. In this review, we have described the key role of epigenetic prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 107 publications
(125 reference statements)
0
17
0
Order By: Relevance
“…Reporter gene assays showed that RuvBL1 overexpression significantly decreased AP-1 luciferase activity in TRAIL-treated cells ( Figure 3A ). AP-1 activity responds to extracellular stimulation mainly via JNK and ERK pathways ( 31 ). However, RuvBL1 overexpression did not affect JNK and ERK activation induced by TRAIL ( Figure 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…Reporter gene assays showed that RuvBL1 overexpression significantly decreased AP-1 luciferase activity in TRAIL-treated cells ( Figure 3A ). AP-1 activity responds to extracellular stimulation mainly via JNK and ERK pathways ( 31 ). However, RuvBL1 overexpression did not affect JNK and ERK activation induced by TRAIL ( Figure 3B ).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, disordered regions within TFs, which become structured upon interaction with binding partners (“coupled folding and binding”) may also represent attractive therapeutic targets. Indeed, these regions have a higher proportion of potential cavities and can more easily adjust to small molecules [ 65 , 66 , 67 , 68 , 69 ]. Below we discuss some potential approaches to target AP-1 TFs in MM ( Figure 2 and Table 2 ).…”
Section: Targeting Ap-1 Tfs For MM Therapymentioning
confidence: 99%
“…Epigenetic alterations activate or suppress AP-1 activities and offer the opportunity to selectively target AP-1 transcriptomes [ 68 ].…”
Section: Targeting Ap-1 Tfs For MM Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the AP-1 pathway is regulated by the transcription factor AP-1, which is responsible for regulating cell differentiation, cell cycle progression, and apoptosis. The AP-1 pathway consists of c-Fos and c-Jun families, and its transcriptional activation is mediated through the dimerization of these two subunits [ 17 , 18 , 19 , 20 , 21 ]. Originally located in the cytosol, c-Fos and c-Jun translocate into the nucleus and dimerize after they are activated by their upstream kinases, mitogen-activated protein kinases (MAPKs).…”
Section: Introductionmentioning
confidence: 99%